Economic Value Added of Ant Sugar and Printed Palm Sugar (Arenga pinnata Merr.) in Cikadu District, Cianjur Regency - Yuliana Samantha; Euis Dasipah; Ronnie Susman Natawidjaja; Tomy Perdana; Firman Sutarman Hasan; Febry Syaman Hasan (Greenation International Journal of Economics and Accounting, 2026)
Indonesian people know palm sugar as one of natural sweeteners, it is used as a supplement to food and drink because it has a distinctive flavor not found in sugar cane. One diversification of palm sugar products is ant sugar. It is a palm sugar in form of a crystal. It is said to be called ant sugar because it looks like an ant house. Process of making it is longer than coconut sugar or palm sugar. This research compared compared it to printed sugar and palm sugar based on socioeconomic conditions and agribusiness income. Samples using Solvin's Formula, 64 ant sugar and 30 scattered sugar farmers’ respondents. Conclusions:  Value-added ratio of palm sugar businesses is said to be still low but still profitable; Income of palm sugar plantation is difference between income and total production cost and average income is IDR 2,295,537.78 each month; Income of palm sugar cultivation is difference between income and total production cost and average income is IDR 1,135,535.90 each month.